Prevalence of drug use among students in mainland China: A systematic review and meta-analysis for 2003–2013. (1st May 2018) - Jia, Zhongwei; Jin, Yuanyuan; Zhang, Lingling; Wang, Ziyun; Lu, Zuhong
Highlights: The first study to estimate prevalence drug use among attending student in China. A high rate of illicit drugs uses among attending students (2.1%). A high rate of Sedative-hypnotics abuse among attending students (6.1%). There is pressing need to take further investigation among students in China. Abstract: Background: In response to calls to reassess and reform international drug policy, we estimated the prevalence of drug use among students in China from 2004 to 2013 through a systematic review and meta-analysis. Methods: We systemically identified and reviewed published studies on illicit drug use and abuse of sedative-hypnotics among students in China. We estimated the prevalence of drug use among students using a meta-regression model. The trends in drug use and any geographic differences were assessed using multilevel models, and the association between drug use and sedative-hypnotics abuse was also examined. Results: The pooled prevalence of illicit drug use and sedative-hypnotics abuse in students was 2.10% (95% CI: 1.80–2.50) and 6.10% (95% CI: 5.10–7.20). A significant decrease in the prevalence of illicit drug use was observed in 2009–2013 (OR = 0.28, 95% CI: 0.25–0.32). Students in higher grades showed a higher prevalence of both illicit drug use and sedative-hypnotics abuse than those in lower grades. Provincial differences in illicit drug use (OR = 2.66, 95% CI: 1.24–5.73) and sedative-hypnotics abuse (OR = 1.37, 95% CI: 1.05–1.79) were identified. The geographical area of illicit drug use was observed to be expanding. Conclusion: Prevalence of drug use among students is twice as high as in the general population of adults in China, indicating that drug use is becoming an urgent public health issue among the younger population. Further investigation among school students is needed.